Assistência estudantil e inclusão digital: da implementação à institucionalização de ações na UFSM - Müller, Adauton Ezequiel (2022)
This study, linked to the Graduate Program in Public Policy and Educational Management - Professional Master’s Degree of the Federal University of Santa Maria (UFSM), discusses student assistance, specifically digital inclusion, considering the context of Higher Education. It aims to analyze the actions of digital inclusion related to the Student Assistance of UFSM, seeking to understand its importance and its influence for the permanence of students in the institution. As a theoretical framework presents the legal frameworks of the construction of student assistance policy and important elements for the debate on digital inclusion. This is a qualitative research, case study type. It is characterized as implicated research, because it involves the context of professional activity of the researcher. It was held at UFSM, involving undergraduate students attended by the student assistance policy, the managers of this policy and the Technical-Administrative Servers in Education that operationalize the aid digital inclusion, techniques, documentary research, questionnaire and semistructured interview. The data were analyzed using the Discursive Textual Analysis proposed by Moraes and Galiazzi (2007). From the universe of data produced in the study, the following categories emerged: Digital inclusion actions: their importance for the permanence of students and their contribution to the objectives of the PNAES; Aid planning: definitions, limits and complexity of the proposal; The context of implementation of digital inclusion actions; Perceptions about EA and digital inclusion actions in relation to the 2030 Agenda and its SDGs and Regulation of digital inclusion actions: institutionalization. In summary, it is stated that the actions of digital inclusion influence the permanence of students, to the extent that they provide digital access to classes, content, to the REDE, and thus the improvement of learning conditions. They are of fundamental importance and add to the other resources of the AE, providing the conditions for the permanence of students, especially those entering by quotas. Thus, for their contribution to the social role of UFSM and social inclusion, they need to be maintained, that is, institutionalized. Therefore, as a final educational product, it is proposed a Draft Resolution that institutionalizes these aids within the institution for undergraduate students who have access to socioeconomic benefit.